POWER AND POLITICS:: THE IMPACTS OF SETTLER COLONIALISM ON HEALTH INTERVENTIONS TARGETING INDIGENOUS CANADIANS (Canadian Journal of Native Studies, 2026)
Since the colonisation of their land in 1534, Canada’s Indigenouspopulation has suffered adverse health outcomes of colossalmagnitude. The intergenerational impacts of such eventspersist in the current day, with contemporary Indigenous Canadiansexperiencing extreme health disparities in comparisonwith their non-Indigenous counterparts. Consequently,Indigenous Canadians are targeted by numerous health interventionswhich, despite claiming to improve health outcomes,often see no benefit and more concerningly, reinforce negativehealth behaviours and spur discrimination, thereby propagatingCanada’s neo-colonial political agenda. This narrativeessay employs Patricia Hill Collins’ matrix of domination toexplore the power relations underpinning such health interventionsand provides recommendations for reforms withinCanada’s healthcare system. Although Indigenous activismand sovereignty are occurring within the hegemonic and interpersonaldomains of power, the studies analysed herein revealthat many health interventions fail to yield positive results dueto persistent racist legislations and establishments within thestructural and disciplinary domains of power. As such, nationwidepolitical reforms must move beyond encouraging simple‘partnerships’ between Indigenous and Euro-Canadian healthcareofficials, to foster true Indigenous healthcare leadershipand autonomy.